2018
DOI: 10.1136/vetreccr-2017-000569
|View full text |Cite
|
Sign up to set email alerts
|

Primary extraskeletal chondrosarcoma in the axillary region of a dog with review of the literature

Abstract: An eight-year-old, intact male English springer spaniel was presented with a five-month history of right forelimb lameness. MRI revealed a right axillary mass with associated nerve root thickening. Radiographs showed no evidence of bone involvement or pulmonary metastasis. A biopsy was taken of the mass, and histopathological examination was consistent with a high-grade chondrosarcoma. Conservative treatment was elected, and the patient euthanased four months later, after which postmortem examination was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…In comparison, wide complete excision of appendicular chondrosarcomas is shown to be the best prognostic indicator in other veterinary and human literature, which has also held true in other case reports 5,24,26,28,33,34 . A significantly increased survival time was also noted, in a recent literature review by Pennington and others, between medically and surgically managed patients with EMCS, with a MST of 44 days and 11 months, respectively 29 …”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In comparison, wide complete excision of appendicular chondrosarcomas is shown to be the best prognostic indicator in other veterinary and human literature, which has also held true in other case reports 5,24,26,28,33,34 . A significantly increased survival time was also noted, in a recent literature review by Pennington and others, between medically and surgically managed patients with EMCS, with a MST of 44 days and 11 months, respectively 29 …”
Section: Discussionsupporting
confidence: 54%
“…Lung metastases have been shown to correlate with a higher histological grade of the tumour 6,7 . In a recent review, evidence of distant disease was reported in 31% of cases, which was similar to the rate found by Brodey et al in 1974 5,29 . Metastases have also been shown to present within 3–17 months of surgical excision 3,30 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Como, na maioria das vezes, os condrossarcomas são mal vascularizados, eles apresentam áreas de necrose de coagulação ou focos de mineralização e uma ossificação endocondral também pode ser encontrada (THOMPSON; DITTMER, 2017). Nos casos mais agressivos, os condrossarcomas apresentam um caráter altamente infiltrativo com acentuado pleomorfismo celular, áreas com conglomerado de células e ausência de matriz extracelular, figuras de mitoses abundantes e extensa área de necrose (PENNINGTON, 2018).…”
Section: Introductionunclassified